Analisis Kelayakan Usaha Peternakan Sapi Potong Rakyat di Kabupaten Langkat - Ruth Dameria Haloho; Chaula Lutfia Saragih (AGRIMOR, 2021)
This study aims to determine the characteristics and feasibility of smallholder beef cattle business in Langkat Regency. This research was conducted in May 2020. The research method used was a survey method. The sampling technique used in this study was the Multistage Random Sampling Method. Respondents were beef cattle breeders who were taken randomly as many as 80 respondents. The data collection method is the method of observation and direct interviews with breeders. Methods of data analysis are descriptive and quantitative. The results show the characteristics of the breeders, namely the age of the productive age breeders, namely 40-50 years (47 people), the education level of the breeders who were mostly educated in junior high school was 48.75% and the breeding experience was 11-20 years as many as 51 people (63.75%). . Business feasibility, namely an ROI of 27.45%, is greater than the interest rate on Bank BRI's deposit interest of 4%. NPV of IDR 452,758 is worth greater than zero. The Net BC ratio value of 1.01 is greater than 1. IRR of 14,05%, is greater than the interest rate on Bank BRI's credit interest of 6%. The conclusion of this study is that the business is declared financially feasible because it is able to generate a return on investment and the revenue received is greater than the expenditure so that the business is profitable and feasible to develop.